1995
DOI: 10.1039/p29950001443
|View full text |Cite
|
Sign up to set email alerts
|

Precise PPP molecular orbital calculations of excitation energies of polycyclic aromatic hydrocarbons. Part 1. On the correlation between the chemical softness and the absolute hardness

Abstract: By considering the character of n-conjugated systems of polycyclic aromatic hydrocarbons (PAHs), it has become apparent that a new two centre electron repulsion integral, new-y, which takes the chemical softness of a n-conjugated system into account is useful for the Pariser-Parr-Pople molecular orbital (PPP MO) calculations of the excitation energy of the p-band of PAHs. Employing the correlation between the chemical softness and the absolute hardness, the method to evaluate the chemical softness parameter k … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 20 publications
(10 reference statements)
0
18
0
Order By: Relevance
“…It has been reported that the l max of conjugated compounds predicted by the INDO/S calculation tends to be shorter than the experimental value as shown in Fig. 6(A) [20]. The difference between the predicted and observed l max of polyacetylenes reaches 30-40 nm at the degree of polymerization is 20.…”
Section: Resultsmentioning
confidence: 85%
“…It has been reported that the l max of conjugated compounds predicted by the INDO/S calculation tends to be shorter than the experimental value as shown in Fig. 6(A) [20]. The difference between the predicted and observed l max of polyacetylenes reaches 30-40 nm at the degree of polymerization is 20.…”
Section: Resultsmentioning
confidence: 85%
“…We defined acenes as aromatic sextet resonance system (ASKS) based on the essential character of their mobile ~t-electrons [7]. On the contrary, the absorption wavelengths of the p-band of zig-zag phenes (phenanthrene, chrysene, picene, and so on) shift toward longer wavelengths more slightly compared with those of acenes, along with the annellation.…”
Section: Methodsmentioning
confidence: 99%
“…On the contrary, the absorption wavelengths of the p-band of zig-zag phenes (phenanthrene, chrysene, picene, and so on) shift toward longer wavelengths more slightly compared with those of acenes, along with the annellation. We defined zig-zag phenes as aromatic sextet alternation system (ASAS), because their ac-electrons trend to localize at the particular positions of the molecular framework [7].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, they reported that this error produced by the conventional PPP method could be greatly improved by the reevaluation of the twocenter electronic repulsion integral (New-g), thus introducing the concept of chemical softness (referred to as New-g PPP). [6][7][8][9][10][11][12] Furthermore, Nakayama and co-worker 13,14) also reported that the shortcomings of NM-g CNDO/S calculations are appreciably absent among the results of the modified CNDO/S and ZINDO (referred to as New-g CNDO/S and New-g INDO/S) calculations, which introduce a New-g using the concept of chemical softness for a number of polycyclic aromatic hydrocarbons. However, the New-g CNDO/S and New-g INDO/S methods cannot be applied to compounds other than p-conjugated aromatic hydrocarbons, because the New-g values have not yet been determined with respect to the p-conjugated compounds containing various hetero atoms, namely, there is a variable k-function for each bonds C-N, C-O, N-N, etc.…”
mentioning
confidence: 99%